2019
DOI: 10.3846/ijspm.2019.7434
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Certification Schemes and Property Values: Evidence From the Hong Kong Prime Commercial Office Market

Abstract: A barrier to green-building development is the uncertainty and scepticism about the financial implications. This study aimed to investigate whether the green-certification schemes help buyers to recognize the benefits of green office buildings by their willingness to pay a premium for such buildings. The study used a hedonic-model based on a sample of 67 prime office buildings (including non-green comparables) certified by HKBEAM, BEAM-Plus and LEED in Hong Kong. The empirical findings suggest that green certi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…This additional investment can lead to higher construction and operating costs compared to conventional buildings. However, green buildings can also provide significant longterm cost savings through reduced energy and water usage, as well as lower maintenance costs (Li et al, 2021;Mangialardo et al, 2019;Porumb et al, 2020;Wadu Mesthrige & Chan, 2019). The level of green premium can vary depending on a number of factors, including the building's location, size, and design, as well as the level of certification sought.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This additional investment can lead to higher construction and operating costs compared to conventional buildings. However, green buildings can also provide significant longterm cost savings through reduced energy and water usage, as well as lower maintenance costs (Li et al, 2021;Mangialardo et al, 2019;Porumb et al, 2020;Wadu Mesthrige & Chan, 2019). The level of green premium can vary depending on a number of factors, including the building's location, size, and design, as well as the level of certification sought.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, green properties are absorbed by the market in less than half the time when compared to those without green certification [14]. The 2019 study that looked at the city of Hong Kong (7.5 m) by Wadu Mesthrige and Chan [15] found that developer and investor stakeholders were uncertain and sceptical about the financial rewards of green certification. The quantitative study tested the factual basis for these inhibiters with the actions of the real estate market.…”
Section: Place-based Contextmentioning
confidence: 99%
“…These studies include research in the US [29]; US and Canada [30]; Singapore [31]; and England [32]. Wadu Mesthrige and Chan [15] looked at prime commercial office buildings in Hong Kong used a hedonic-model of rent and building attributes. A US study conducted in 2018 by Fuerst et al [33] also used a hedonic model.…”
Section: Financial Factorsmentioning
confidence: 99%
“…Among various determinants that have been used in hedonic price models in the Hong Kong HPM literature (e.g., Wadu Mesthrige and Chan, 2019;Wadu Mesthrige et al, 2018), ten important determinants are selected for the current study. Besides, other studies (based on HPM) have used these key variables in their studies.…”
Section: Hedonic Price Model (Hpm)mentioning
confidence: 99%